The optimization of sample treatment for spectral karyotyping with applications for human tumour cells - Loja, Tomáš; Kuglík, Petr; Oltová, Alexandra; Šmuhařová, Petra; Zitterbart, Karel; Bajčiová, Viera; Veselská, Renata (Cytogenetic and genome research, 2007)
Spectral karyotyping (SKY) represents an important tool for the investigation of the complex chromosomal rearrangements (CCRs) in many human malignancies which may be difficult to characterize by conventional banding techniques. The main goal of our work was to optimize the most important steps in the preparation of molecular cytogenetic slides for a SKY protocol. This approach consisted of optimization of both the aging procedure and protease pretreatment of the slides, with special regard given to the preservation of chromosome structure and shape, as well as to the intensity of hybridization signals. The best results were obtained with a chemical aging procedure using SSC or ethanol in combination with trypsin pretreatment applied at a higher concentration for a shorter period of pretreatment. A resulting protocol for SKY also applicable to human solid tumour cells was subsequently proposed. The practical potential of the SKY technique was demonstrated on examples of two types of human embryonal tumours--neuroblastoma and Wilms' tumour, in which some kinds of chromosomal aberrations were not detectable by means of classic cytogenetic methods. Copyright 2007 S. Karger AG, Basel.
Keywords: financování organizované; Indoles; spektrální karyotypizace; krevní buňky; Specimen Handling; indoly; Wilmsův nádor; dítě; Wilms Tumor; lidé; hybridizace nukleových kyselin; stárnutí buněk; Spectral Karyotyping; Metaphase; metafáze; proteasy; Financing, Organized; Peptide Hydrolases; Neuroblastoma; Nucleic Acid Hybridization; Child; Blood Cells; neuroblastom; odběr biologického vzorku; Cellular Senescence; Humans